2011
DOI: 10.1371/journal.pone.0021095
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of rDNA Transcription by Proto-Oncogene PELP1

Abstract: BackgroundProline-, glutamic acid-, and leucine-rich protein (PELP1) is a novel nuclear receptor coregulator with a multitude of functions. PELP1 serves as a scaffolding protein that couples various signaling complexes with nuclear receptors and participates as a transcriptional coregulator. Recent data suggest that PELP1 expression is deregulated in hormonal cancers, and that PELP1 functions as a proto-oncogene; however, the mechanism by which PELP1 promotes oncogenesis remains elusive.Methodology/Principal F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Additionally, PARP-1 has been shown to interact with nucleolar proteins and transcriptional coregulators (nucleolin and nucleophosmin) in a number of contexts (64)(65)(66). Recent studies have shown that PELP1 enhances ribosomal DNA (rDNA) transcription (67) and functions in a complex with WDR18, TEX10, and a nucleolar deSUMOylating enzyme to control rRNA processing and ribosome biogenesis (68). Most recently, macroH2A1 has been shown to repress rRNA gene transcription (69).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PARP-1 has been shown to interact with nucleolar proteins and transcriptional coregulators (nucleolin and nucleophosmin) in a number of contexts (64)(65)(66). Recent studies have shown that PELP1 enhances ribosomal DNA (rDNA) transcription (67) and functions in a complex with WDR18, TEX10, and a nucleolar deSUMOylating enzyme to control rRNA processing and ribosome biogenesis (68). Most recently, macroH2A1 has been shown to repress rRNA gene transcription (69).…”
Section: Discussionmentioning
confidence: 99%
“…CDK phosphorylation of PELP1 allows PELP1 to localize to the nucleolus, where it regulates rDNA transcription. The inhibition of CDKs dramatically reduces the localization of PELP1 to the nucleolus and has been shown to decrease rDNA promoter activity (Gonugunta et al 2011). This indicates that PELP1 has an overarching role not only in SR-mediated gene regulation but also in cell division.…”
Section: Pelp1 In Ribosome Biogenesismentioning
confidence: 99%
“…PELP1 has three nucleolar domains (Nuc1: amino acids 79-160; Nuc2: amino acids 423-489; and Nuc 3: amino acids 569-642), which are important not only for the nuclear and nucleolar localization of PELP1, but also for rRNA processing and the activation of rDNA transcription and subsequent ribosome biogenesis (Gonugunta et al 2011). PELP1 has a single RIX1 (rRNA processing/ribosome biogenesis) (amino acids 73-224) domain that enables complex formation with proteins IPI1 (TEX10), IPI3 (WDR18), and LASL1 and allows Rea1 AAA ATPase to associate with the 60S ribosomal subunit, a critical step in rRNA processing and ribosome assembly.…”
Section: Nucleolar and Rix1 Domainsmentioning
confidence: 99%
See 2 more Smart Citations